Penerapan Balanced Scorecard di Rumah Sakit Indonesia: Systematic Review - Avenia Dionisia Menna; Nauri Anggita Temesvari (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2022)
A systematic review is a research method that summarizes primary research results to present facts that are more comprehensive and balanced. A balanced scorecard is a concept for measuring the performance of an organization with 4 (four) different perspectives, namely customer perspective, financial perspective, internal business perspective, and learning and growth perspective. The results of the initial article screening using the database literature on google scholar obtained 513 journals, science direct obtained 7 journals and GARUDA obtained 20 journals with the keywords "Balanced Scorecard AND Performance Measurement, OR Balanced Scorecard And Hospital Performance", there are 20 journal articles that discuss the application balanced scorecard as performance measurement in the hospital. Assessment of the quality of literature in this study is by using the SRQR and STROBE instruments. Samples obtained from 20 journal articles are 12 with the results of the research that the financial perspective performance calculation is in the "good" category with a percentage of 68.62%, on the customer perspective performance is in the "good" category with a percentage of 78.78%, the performance of the internal business process perspective is in the "good" category with a percentage of 71.66% and the performance of the learning and growth perspective is in the "good" category with a percentage of 62.5%. From the indicators measured in 4 (four) perspectives on the balanced scorecard, it is obtained that the indicators measured are not uniform or some indicators are not measured in other perspectives.Keywords:Balanced scorecard; Performance measurement; Systematic review;